Application of Situational Leadership Style at PT. Bank Negara Indonesia (Persero) Tbk, Mattoangin Makassar Branch Office - Rifdan, Rifdan; Astuti, Fuji; Niswaty, Risma (Pinisi Business Administration Review, 2022)
It is not possible to manage members of an organization with different personalities, backgrounds, levels of will and abilities, by using only a single leadership. Therefore, dealing with situations or different levels of employee maturity requires different leadership styles. This study aims to determine the Situational Leadership Style applied to PT. Bank Negara Indonesia (Persero) Tbk Mattoangin Makassar Branch Office, in terms of the dimensions of Telling Style, Selling Style, Participating Style and Delegating Style. The research method used is a descriptive research method with a quantitative approach. The data collection techniques used were questionnaires/questionnaires, structured interviews, direct observation, and documents. The sampling technique used was non-probability sampling with saturated sampling (census) as many as 42 employees. Respondents' answers were analyzed using descriptive analysis through the distribution of frequencies and percentages. The results of this study indicate that the application of the Situational Leadership Style which consists of four dimensions, namely the Telling Style is quite good and has a percentage of 77.30%. Selling Style is good and has a percentage of 84, 32%. Participating Style is very good and has a percentage of 85, 95%. Meanwhile, Delegating Style is good and has a percentage of 80.00%.